Malaysian hospitality industry: Graduates’ justifications for leaving the industry - Ahmad, Rozila; Rashid, Basri; Mohd Shariff, Nurhazani (Universiti Utara Malaysia Press, 2014)
Continuous skilled-employee shortage has been reported in the hospitality industry despite the mushrooming growth of higher learning institutions offering the Bachelor of Hospitality Management (BHM) programme.The purpose of this study is to assess the BHM graduates’ areas of employment and their justification for not seeking employment or leaving the hospitality industry.To meet the purpose, a quantitative research paradigm supported by open-ended questions was used. This study focused on Universiti Utara Malaysia (UUM) BHM graduates.The findings revealed that the UUM BHM graduates’ Islamic faith plays a significant role in the religious Muslim graduates’ career paths.However, as widely documented in the literature, unattractive compensation in the hospitality industry appears to be the most important reason for graduates to seek employment in other industries. This is followed by poor career development opportunities and working conditions.Information from this study may help remedy the continuous shortage of skilled employees in the industry.It may also ensure the graduates’ ability to secure suitable jobs.In addition, it indirectly helps in the initiative to improve the BHM curriculum.